2003
DOI: 10.1001/jama.289.14.1792
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss With Self-help Compared With a Structured Commercial Program

Abstract: Context Although commercial weight loss programs provide treatment to millions of clients, their efficacy has not been evaluated in rigorous long-term trials. Objective To compare weight loss and health benefits achieved and maintained through self-help weight loss vs with a structured commercial program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
312
4
17

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(359 citation statements)
references
References 26 publications
26
312
4
17
Order By: Relevance
“…Participants in the structured weight loss arm received incentives in the form of vouchers for the cost of the commercial programme and had contact with the researchers every 1-2 weeks over the 2-year period. 15 In our study, there was no significant difference in weight loss between the two intervention groups over the 12 months. There was a trend however for the FBI group to maintain weight loss compared to the other two groups.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Participants in the structured weight loss arm received incentives in the form of vouchers for the cost of the commercial programme and had contact with the researchers every 1-2 weeks over the 2-year period. 15 In our study, there was no significant difference in weight loss between the two intervention groups over the 12 months. There was a trend however for the FBI group to maintain weight loss compared to the other two groups.…”
Section: Discussioncontrasting
confidence: 49%
“…That is, minimal inclusion and exclusion criteria were applied, incentives were not provided and dietetic staff provided the interventions within normal workplace requirements. This is in contrast to previous studies, which have provided participants with enticing incentives to maintain involvement 15 or applied stringent eligibility criteria, 16,28 which limit generalisability of the results.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These investigators concluded that adherence was a stronger predictor of weight loss success than diet group assignment, but the 12-month dropout rates of 35-50% among their four diet groups present a limitation. Heshka et al 17 reported a significant association between adherence to the Weight Watcher program and weight loss success but adherence was assessed by self-reported attendance. Finally, Knauper et al 15 examined the relationship between adhering to self-set dieting rules and weight loss and concluded that adherence was associated with weight loss success.…”
Section: Discussionmentioning
confidence: 99%
“…Even the few studies that have examined the associations between dietary adherence and weight loss were constrained by a number of limitations such as self-reported measure of adherence measure, small sample sizes, low retention rate and short study follow-up period. 10,[15][16][17] Therefore, to address some of the potential limitations of previous work, we performed the present analyses to determine the level of adherence from a 1-year randomized clinical trial comparing the effectiveness of four popular diets in overweight/obese women using carefully measured diet data and to examine the association between the dietary adherence and magnitude of weight loss.…”
Section: Introductionmentioning
confidence: 99%